2004
DOI: 10.1007/s00592-004-0142-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of silent myocardial ischemia in type 2 diabetic patients and the relation with poor glycemic control

Abstract: The aim of the study was to investigate the frequency of silent myocardial ischemia in type 2 diabetic patients without any clinical or laboratory findings of myocardial ischemia and to examine the related factors for silent myocardial ischemia. A total of 116 type 2 diabetic patients (82 women) with a disease duration of 5-20 years were included in the study. All patients underwent stress and resting myocardial perfusion single-photon emission computed tomographic (SPECT) study with (99m)Tc-MIBI. Coronary ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
3
17
1
2
Order By: Relevance
“…Diabetic patients with asymptomatic CAD have a higher cardiac mortality risk than those with the symptomatic disease (25). Performing routine screening for asymptomatic CAD in all patients with type 2 DM is debatable for several reasons (26-28). CAD screening might identify individuals who could benefit from anti-ischemia therapy or from revascularization, and specifically those with left main or severe multi-vessel disease (28).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients with asymptomatic CAD have a higher cardiac mortality risk than those with the symptomatic disease (25). Performing routine screening for asymptomatic CAD in all patients with type 2 DM is debatable for several reasons (26-28). CAD screening might identify individuals who could benefit from anti-ischemia therapy or from revascularization, and specifically those with left main or severe multi-vessel disease (28).…”
Section: Discussionmentioning
confidence: 99%
“…Araz et al 16 (2004) showed that poor glycemic control, as reflected by HbA 1c levels, may be a factor related to SMI in diabetic patients. A significant correlation between silent CAD and postprandial blood glucose level was observed in an article published in 2003 by Gokcel et al 17 In contrast, JanandDelenne et al 18 (1999) had reported that there was no correlation between SMI and duration of diabetes nor HbA 1c .…”
Section: Discussionmentioning
confidence: 99%
“…There are also several studies reporting only on positive predictive values of 44-100% from patients submitted to left heart catheterization because of an abnormal myocardial perfusion SPECT [30,53,[55][56][57][58][59]61,[64][65][66]70,71,78,79]. In general, the sensitivity and specificity values of MPI in asymptomatic diabetic subjects are not as good as those found in other series with mixed asymptomatic and symptomatic diabetic populations (80-86% and 56-87%, respectively) [24,80].…”
Section: Stress Myocardial Perfusion Imagingmentioning
confidence: 49%